Banks' Legal Responsibilities In Handling Non-Performing Loans: A Regulatory Perspective And Its Implementation In Indonesia - Febiwati, Tritinta Palupi Febiwati; Hartono Paulus, Darminto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Non-performing loans (NPLs) are a major challenge for the banking industry because they have the potential to threaten the financial stability of banks and the national economy. This study aims to evaluate the legal responsibility of banks in handling non-performing loans in Indonesia, focusing on the effectiveness of applicable regulations, such as the Banking Law, Financial Services Authority (OJK) regulations, and the application of Basel III principles. Through a normative-empirical approach and case analysis from several banks in Indonesia, this study finds that existing regulations are quite effective in reducing the number of NPLs if implemented with high compliance. However, there are operational, legal, and economic challenges that affect the optimal implementation of regulations. The study recommends improved risk management and better supervision to support banks in fulfilling their legal responsibilities regarding non-performing loans.